Measuring Proximity: A Post-Interpretive Diagnostic Experiment in Art Criticism A Diagnostic Lens on Ethical Witnessing in Art Criticism - Vale, Dorian (Museum of One, 2026)
Contemporary art criticism often advances by way of interpretive extraction. Works are translated into meanings, themes, intentions, and arguments, which then circulate with remarkable efficiency through institutional language. This practice, for all its fluency, carries an unexamined cost: the quiet displacement of the viewer, the compression of encounter into explanation, and the steady accumulation of linguistic force where restraint might have sufficed. _Measuring Proximity_ proposes a post-interpretive diagnostic tool situated within the framework of Post-Interpretive Criticism (PIC). It does not ask whether an interpretation is correct, persuasive, or useful. Instead, it attends to posture, how critical language positions itself in relation to the artwork, how closely it remains, how quickly it resolves, and how readily it aligns. The framework emerges from a refusal of rigid disciplinary boundaries. It proceeds from the conviction that once inquiry is pursued with sufficient depth, the familiar divisions between philosophy, criticism, rhetoric, ethics, and analysis begin to collapse, revealing a shared terrain of attention and care. In this sense, the diagnostic experiment does not belong to a single “subject,” nor does it attempt to formalize one. Five diagnostic indices, Rhetorical Density (RD), Interpretive Load Index (ILI), Viewer Displacement Ratio (VDR), Ethical Proximity Score (EPS), and Institutional Alignment Indicator (IAI), are introduced as reflective instruments for tracing the behavior of language rather than adjudicating its claims. The framework is intentionally non-prescriptive and exploratory, offered in the spirit of a serious experiment, one that treats measurement not as authority, but as curiosity. These measures do not seek to replace interpretation, nor to govern style or method. They operate as a mirror, rendering visible the pressures already at work within critical discourse. What emerges is not a system of judgment, but a way of noticing: a playful yet disciplined attempt to see where explanation begins to outweigh encounter, and where proximity quietly gives way to possession. Rhetorical density enters this framework by way of inheritance rather than invention. Its articulation as a formal, measurable feature of language was first developed by Mandar Marathe and introduced to the research community through presentations at venues such as QUALICO 2025 at Masaryk University and the Digital Humanities Conference at SOAS University of London. Later implementations, including the BALAGHA Score (2025–2026), extended its use toward the measurement of rhetorical richness in Arabic-language texts. Here, rhetorical density functions simply as a descriptive register of linguistic intensity. The remaining indices: Interpretive Load Index (ILI), Viewer Displacement Ratio (VDR), Ethical Proximity Score (EPS), and Institutional Alignment Indicator (IAI), all emerge from within Post-Interpretive Criticism itself and belong specifically to its diagnostic orientation. The framework is not intended to guide the production of criticism, nor does it imply an ideal direction or outcome; it functions only as a means of reflecting on critical language after it has already been written. Post-Interpretive Criticism, Stillmark Theory, Message-Transfer Theory, MTT, Misplacement, Displacement, Aesthetic Displacement Theory, Theory of Misplacement, Absential Aesthetics, Witness Aesthetics, Adab for Art, Hauntmark Theory, Spiritual Criticism, Presence-Based Criticism, Custodianship of Art, Art as Ontology, Aesthetic Recursion Theory, Aesthetic Recursion, Viewer as Evidence Theory, Restraint in front of art, Moral proximity, Interpretive silence, Erasure as ethics, Temporal scarcity, Silence as method, Ontology of beauty, Aesthetic mercy, Language as violence, Art encounter ethics, Epistemology of witness, Philosophy of Art, Aesthetics, Art Theory, Contemporary Aesthetics, Comparative Aesthetics, Phenomenology and Art, Ethics in Art Criticism, Interpretation and Meaning, Criticism and Reception Theory, Epistemology of Art, Visual Culture Studies, Dorian Vale, Founder of Post-Interpretive Criticism, Post-Aesthetic Critic, Independent Philosopher of Art, Museum of One, Art Writer and Theorist, Aesthetic Philosopher, Custodian of Witness Aesthetics, Spiritual Aesthetics Movement, The Doctrine of Post-Interpretive Criticism, The Custodian’s Oath, The Canon of Witnesses, Art as Truth, Art as Presence, The Viewer as Evidence, Interpretation vs. Witnessing, Language as Custody, Erasure as Afterlife, Museum of One Manifesto, Alternative art criticism, New art criticism movement, Ethical art theory, Criticism beyond interpretation, Slow looking philosophy, Quiet philosophy of art, Radical art restraint, Witness over interpretation, Interpretive Restraint, The Journal of Post-Interpretive criticism, The Journal of Post-Interpretive criticism ISSN 2819-7232), The Journal of Post-Interpretive Criticism (Q136530009), Interpretive Load Index (ILI) (Q137709526), Viewer Displacement Ratio (VDR) (Q137709583) , Ethical Proximity Score (EPS) (Q137709600) , Institutional Alignment Indicator (IAI) (Q137709608)
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://doi.org/10.5281/zenodo.17069115 https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 https://osf.io/gpwnq https://osf.io/xa5jw/ https://osf.io/zhnre/ https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.17605/OSF.IO/ZHNRE
Keywords: Post-Interpretive Criticism; Stillmark Theory; Message-Transfer Theory; MTT; Misplacement; Displacement; Aesthetic Displacement Theory; Theory of Misplacement; Absential Aesthetics; Witness Aesthetics; Adab for Art; Hauntmark Theory; Spiritual Criticism; Presence-Based Criticism; Custodianship of Art; Art as Ontology; Aesthetic Recursion Theory; Aesthetic Recursion; Viewer as Evidence Theory; Restraint in front of art; Moral proximity; Interpretive silence; Erasure as ethics; Temporal scarcity; Silence as method; Ontology of beauty; Aesthetic mercy; Language as violence; Art encounter ethics; Epistemology of witness; Philosophy of Art; Aesthetics; Art Theory; Contemporary Aesthetics; Comparative Aesthetics; Phenomenology and Art; Ethics in Art Criticism; Interpretation and Meaning; Criticism and Reception Theory; Epistemology of Art; Visual Culture Studies; Dorian Vale; Founder of Post-Interpretive Criticism; Post-Aesthetic Critic; Independent Philosopher of Art; Museum of One; Art Writer and Theorist; Aesthetic Philosopher; Custodian of Witness Aesthetics; Spiritual Aesthetics Movement; The Doctrine of Post-Interpretive Criticism; The Custodian’s Oath; The Canon of Witnesses; Art as Truth; Art as Presence; The Viewer as Evidence; Interpretation vs. Witnessing; Language as Custody; Erasure as Afterlife; Museum of One Manifesto; Alternative art criticism; New art criticism movement; Ethical art theory; Criticism beyond interpretation; Slow looking philosophy; Quiet philosophy of art; Radical art restraint; Witness over interpretation; Interpretive Restraint; The Journal of Post-Interpretive criticism; The Journal of Post-Interpretive criticism ISSN 2819-7232); The Journal of Post-Interpretive Criticism (Q136530009); Interpretive Load Index (ILI) (Q137709526); Viewer Displacement Ratio (VDR) (Q137709583); Ethical Proximity Score (EPS) (Q137709600); Institutional Alignment Indicator (IAI) (Q137709608)